2012
DOI: 10.1089/aid.2012.0262
|View full text |Cite
|
Sign up to set email alerts
|

RMP-02/MTN-006: A Phase 1 Rectal Safety, Acceptability, Pharmacokinetic, and Pharmacodynamic Study of Tenofovir 1% Gel Compared with Oral Tenofovir Disoproxil Fumarate

Abstract: This study was designed to assess the safety, acceptability, pharmacokinetic (PK), and pharmacodynamic (PD) responses to rectal administration of tenofovir (TFV) 1% vaginally formulated gel and oral tenofovir disoproxil fumarate (TDF). This study was designed as a phase 1, randomized, two-site (United States), double-blind, placebo-controlled study of sexually abstinent men and women. Eighteen participants received a single 300-mg exposure of oral TDF and were then randomized 2:1 to receive a single and then s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
177
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 132 publications
(183 citation statements)
references
References 36 publications
6
177
0
Order By: Relevance
“…We have shown separately that seminal fluid does not impact the in vitro antiviral activity of MIV-150 in vaginal tissues (P. Barnable and N. Teleshova, unpublished data). Further supporting the potential predictive value of product testing in explants, the TFV gel inhibited HIV in the tissues (45,46) and was shown to reduce HIV incidence by 39% overall (47). TFV gel was not effective in the VOICE trial (48), possibly due to lack of adherence as determined by PK studies (7).…”
Section: Discussionmentioning
confidence: 97%
“…We have shown separately that seminal fluid does not impact the in vitro antiviral activity of MIV-150 in vaginal tissues (P. Barnable and N. Teleshova, unpublished data). Further supporting the potential predictive value of product testing in explants, the TFV gel inhibited HIV in the tissues (45,46) and was shown to reduce HIV incidence by 39% overall (47). TFV gel was not effective in the VOICE trial (48), possibly due to lack of adherence as determined by PK studies (7).…”
Section: Discussionmentioning
confidence: 97%
“…http://dx.doi.org/10.1101/008607 doi: bioRxiv preprint first posted online Sep. 1, 2014; logical sense given that tenofovir is a DNA chain terminator, with possible off-target effects in human cells 35 , and that topical application achieves at least one hundred-fold higher active drug concentrations in the mucosa than oral administration of 300 mg tenofovir disoproxil fumarate 7,36 . Moreover, tenofovir caused similar changes in primary vaginal epithelial cells cultured from several healthy women.…”
Section: Figure 5 Quantification Of Mitochondriaassociated Parametersmentioning
confidence: 99%
“…In addition, a recent metaanalysis demonstrated that the estimated per-act human immunodeficiency (HIV) transmission risk (per 10,000 exposures) for RAI is 138, compared to 11, 8, and 4 for insertive anal intercourse, receptive penile-vaginal intercourse, and insertive penile-vaginal intercourse, respectively (10). The risk of HIV acquisition via unprotected RAI may be further exacerbated through the improper use of vaginal microbicide gels or high osmolality personal lubricants in the rectal compartment, which have been shown to cause cellular inflammation and epithelial damage (11)(12)(13)(14)(15)(16)(17)(18)(19). These studies collectively highlight a need for a microbicide formulation that is specifically designed for safe application in both the vaginal and rectal compartments and that may also serve as a lubricant.…”
mentioning
confidence: 99%